PHYSICAL THERAPISTS ATTITUDES AND DIAGNOSTIC APPROACH ON ASSESSING CHRONIC LOW BACK PAIN PATIENTS: A MULTICENTER CROSSSECTIONAL STUDY IN KARACHI. - Marina1 , Khowla Shah2 , Barirah muneer3 , Fadwa Tariq4 , Nooria Naeem Dar5 , Huma Mehrin6 , Hira Naz7 , Muhammad Anees Farooque8., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT BACKGROUND: Globally, the chronic low back pain is a highly prevalent condition that affects about 80% of the population at some point in their life. OBJECTIVE: To explore the Physical therapists current attitudes and diagnostic approach on assessing chronic low back pain patients. METHODS: The study was a Cross-sectional survey conducted in Karachi from November 2019 to February 2020. The sampling technique used was non probability, purposive sampling technique, and the sample size was determined using OPEN EPI Version 3.0 software, which estimated a sample size of 126 based on a margin of error of 5% and a confidence level of 95%. Participants were recruited from Dow institute of physical medicine and rehabilitation, Dow University and hospital ojha campus, Jinnah postgraduate medical center and Dr. Ziauddin hospital. Data collection was carried out through a selfStructured questionnaire. RESULTS: Overall 126 physical therapists were included in this study. Their mean age was 26.91 ± 5.5 years. The Majority (61.9%) were females with a male to female ratio of 1:1.6.The Greater numbers of the subjects (55.6%) were having only one year of experience whereas 22.2% in each group has two and three years of experience. The large number of PTs (82.6%) believes that physical therapy assessment should include the screening of red flags; similarly, 81.7% of PTs were of the opinion that diagnosing a condition is part of the physical therapy practice. 79.4% of PTs allow their patients to talk freely without interruption about their problem. However, 76.9% and 74.3% focus on the physician’s diagnosis and their referral card. CONCLUSION: The study explored physical therapists' attitudes and diagnostic practices in assessing chronic low back pain patients. While many acknowledged the importance of biopsychosocial factors, mechanical aspects still received significant attention. The study suggests the need for more holistic assessment skills, reduced reliance on lab investigations, and interdisciplinary collaboration.